PENERAPAN KONSEP CYBER NOTARY DI INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 2 TAHUN 2014 - BENNY BENNY (PREMISE LAW JURNAL, 2015)
Rapid development of information technology and communication in Indonesia has the impact on various fields, including on notarial law. It can be seen in the application of cyber notary concept which increases the effectiveness and the efficiency of a Notary. The result of the research showed that a notary’s authority in certifying electronic transaction as stipulated in Article 15, paragraph 3 of Law No. 2/2014 is the authority to print and to legalize the printed letters and/or certificates by using the system of Ditjen AHU online, and definition of Request in Permenhumkam No. 5/2014 is not correct because the fact is that Ditjen AHU online allows the applicant, either individually or together, without giving the authority to someone else, to get the request and the authorization for Foundation legal entity. It is recommended that definition of Request in Permenkumham No. 5/2014 should be corrected. Keywords: Cyber Notary, Notary, SABH